Health Counseling About Sexually Transmitted Diseases : Penyuluhan Kesehatan Tentang Penyakit Menular Seksual (PMS) - Nur Indah Purnamasari; Juminten Saimin; Rahmawati; Adius Kusnan (Yayasan Ahmar Cendekia Indonesia, 2022)
Sexually Transmitted Diseases (STDs) or also known as sexually transmitted infections (STIs) are infections that are generally transmitted through unsafe sex. The purpose of this community service is to increase public knowledge about sexually transmitted diseases (STDs). The method used is counseling with lectures, discussions, and questions and answers as well as pre and post tests about sexually transmitted diseases (STDs). The counseling participants were pregnant women who visited the KIA Poly Hospital of Aliyah Kendari Hospital as many as 20 people. The result was that the participants were very enthusiastic in watching and participating in the PkM activities. The pre-test of participants' knowledge was carried out by the service team and after the counseling, the mother's knowledge was also measured. The conclusion of this service is that there is an increase in knowledge of pregnant women about sexually transmitted infections (STDs).